2018
DOI: 10.1111/hae.13624
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in paediatric haemophilia B patients treated with rIX‐FP

Abstract: IntroductionFrequent infusions and bleeds can impact on the health‐related quality of life (HRQoL) of paediatric haemophilia B patients. rIX‐FP (IDELVION®) is a fusion protein linking recombinant factor IX with recombinant albumin, and is associated with low bleeding rates with a weekly regimen, which could improve HRQoL.AimsTo measure the effect of rIX‐FP prophylaxis on the HRQoL of paediatric patients and treatment satisfaction in their caregivers using the Haemo‐QoL and Hemo‐SATP questionnaires, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…In the UK, 90.9% of patients who switched to prophylaxis with rIX-FP received once-weekly prophylaxis, which was in line with published guidance on prophylaxis with EHL coagulation factor concentrates from the UK Haemophilia Centres Doctors' Organisation [19]. Reduced dosing frequency may improve treatment adherence and has the potential to improve treatment experience by reducing treatment burden [20]. The higher trough levels achieved with rIX-FP also have the potential to improve patient management and allow the patient to live a more active lifestyle [21].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the UK, 90.9% of patients who switched to prophylaxis with rIX-FP received once-weekly prophylaxis, which was in line with published guidance on prophylaxis with EHL coagulation factor concentrates from the UK Haemophilia Centres Doctors' Organisation [19]. Reduced dosing frequency may improve treatment adherence and has the potential to improve treatment experience by reducing treatment burden [20]. The higher trough levels achieved with rIX-FP also have the potential to improve patient management and allow the patient to live a more active lifestyle [21].…”
Section: Discussionsupporting
confidence: 53%
“…The higher trough levels achieved with rIX-FP also have the potential to improve patient management and allow the patient to live a more active lifestyle [21]. While treatment efficacy should always remain the most important outcome when selecting a treatment regimen, the enhanced features of rIX-FP are allowing patients with haemophilia the opportunity to live a healthier and less burdensome life [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have already demonstrated an improvement in the QoL of patients treated with EHL FIX products. 15,16 Additionally, improving QoL was reported as the most frequent reason to switch to an EHL product according to real-world data collected in Canada. 17…”
Section: Discussionmentioning
confidence: 99%
“…12 Clinical trial outcomes have shown for both EHL recombinant FVIII and FIX drugs that prophylaxis regimens are associated with very low annualized bleeding rates (ABRs) compared to on-demand treatment. 17,18 EHL products have been licensed at different times in the USA and Europe. 17,18 EHL products have been licensed at different times in the USA and Europe.…”
mentioning
confidence: 99%
“…11,[13][14][15][16] These results make such therapies significantly less distressing to the patient (particularly in the case of FIX) and are likely to improve their quality of life. 17,18 EHL products have been licensed at different times in the USA and Europe. In the USA, EHL products were available much earlier than in Europe due to the differences between US Food and Drug Administration (FDA) and European Medicines Agency (EMA) regulations for authorizing new products.…”
mentioning
confidence: 99%